Positive electrode and secondary battery

By adopting a double-layer structure in the positive electrode active material layer of the secondary battery and using positive electrode active materials with different porosity and particle sizes, the problem of insufficient performance of the existing secondary battery is solved, and higher energy density and battery life are achieved.

CN119487642APending Publication Date: 2025-02-18LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380046580.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-04
Filing Date
2023-10-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The energy density, fast charging performance and battery life performance of existing secondary batteries are insufficient, and improper material combination may have an adverse impact on battery performance.

Method used

A layer of positive electrode active material with a two-layer structure is adopted, wherein the first layer has a different porosity than the second layer, and contains a single particle and a positive electrode active material with a particle size greater than a single particle in each layer to optimize the resistance characteristics.

Benefits of technology

By adjusting the type and porosity of the active material, the resistance characteristics of the battery are improved, energy density, fast charging performance and battery life are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487642A_ABST
    Figure CN119487642A_ABST
Patent Text Reader

Abstract

The present invention relates to a secondary battery including a positive electrode for a secondary battery, and a method for manufacturing a positive electrode for a secondary battery. The positive electrode includes: a current collector; a first positive electrode active material layer disposed on the current collector; and a second positive electrode active material layer disposed on the first positive electrode active material layer, in which the first positive electrode active material layer and the second positive electrode active material layer each include a single-particle positive electrode active material and a positive electrode active material having a particle size larger than that of the single-particle positive electrode active material, and wherein a porosity of the first positive electrode active material layer is different from a porosity of the second positive electrode active material layer, or a pore area ratio in a cross-sectional image of the second positive electrode active material layer is 1.05 to 3 times a pore area ratio in a cross-sectional image of the first positive electrode active material layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0128886 filed on October 7, 2022, in the Korean Intellectual Property Office and Korean Patent Application No. 10-2023-0131799 filed on October 4, 2023, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a positive electrode for a secondary battery and a secondary battery including the positive electrode. Background Art

[0003] Secondary batteries are commonly used not only in portable devices but also in electric vehicles (EVs) or hybrid electric vehicles (HEVs) driven by an electric driving source.

[0004] Secondary batteries are drawing attention as a new energy source that improves eco-friendliness and energy efficiency because of major advantages in that the use of fossil fuels is significantly reduced and in that the use of energy does not generate byproducts.

[0005] Generally, a secondary battery includes a positive electrode, a negative electrode, a separator and an electrolyte interposed between the positive electrode and the negative electrode, etc. In addition, electrodes such as the positive electrode and the negative electrode may have an electrode active material layer disposed on a current collector.

[0006] As the use of secondary batteries increases, various battery performances are required. In order to improve battery performance, attempts are being made to control the composition of active materials or additives of the positive or negative electrode active material layer. However, the wrong combination of materials may have an adverse effect on the performance of the final battery. Therefore, it is necessary to study the combination of positive and negative electrode materials to improve battery performance. Summary of the invention

[0007] [Technical issues]

[0008] The present invention is directed to providing a positive electrode for a secondary battery and a secondary battery including the same, the positive electrode providing improved energy density, fast charging performance, and improved battery life performance.

[0009] [Technical solution]

[0010] An exemplary embodiment of the present invention provides a positive electrode for a secondary battery, comprising: a current collector; a first positive electrode active material layer disposed on the current collector; and a second positive electrode active material layer disposed on the first positive electrode active material layer, wherein the first positive electrode active material layer and the second positive electrode active material layer each include a single-particle positive electrode active material and a positive electrode active material having a particle size greater than that of the single-particle positive electrode active material, and wherein the porosity of the first positive electrode active material layer is different from the porosity of the second positive electrode active material layer.

[0011] Another exemplary embodiment of the present invention provides a positive electrode for a secondary battery, comprising: a current collector; a first positive electrode active material layer disposed on the current collector; and a second positive electrode active material layer disposed on the first positive electrode active material layer, wherein the first positive electrode active material layer and the second positive electrode active material layer each include a single-particle positive electrode active material and a positive electrode active material having a particle size greater than that of the single-particle positive electrode active material, and wherein a pore area ratio in a cross-sectional image of the second positive electrode active material layer is 1.05 to 3 times the pore area ratio in a cross-sectional image of the first positive electrode active material layer.

[0012] Another exemplary embodiment of the present invention provides a secondary battery including the above-described positive electrode for a secondary battery, a negative electrode, and a separator.

[0013] [Beneficial Effects]

[0014] According to the exemplary embodiments described in this specification, the positive electrode active material layer has a two-layer structure, and the resistance characteristics of the battery may be improved by controlling the type of active material and the porosity of each layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a graph showing resistance characteristics as a function of the state of charge (SOC) of batteries prepared in Examples and Comparative Examples. DETAILED DESCRIPTION

[0016] Hereinafter, in order to better understand the present invention, the present invention will be described in more detail. The present invention can be implemented in various different forms and is not limited to the following exemplary embodiments. The terms or words used throughout the specification and claims should not be interpreted as limited to their ordinary or dictionary meanings, but should be interpreted as having meanings and concepts consistent with the technical ideas of the present invention based on the concept that the inventor can appropriately define the words or terms to best explain the principles of the present invention.

[0017] It should also be understood that when used in this specification, the terms "includes", "comprising" or "having" specify the presence of stated features, integers, steps, constituent elements and / or combinations thereof, but do not exclude the presence or addition of one or more other features, integers, steps, constituent elements and / or combinations thereof.

[0018] In addition, it should be understood that when an element such as a layer is referred to as being "on" another element, it can be "directly" "on" the other element, or intervening elements may also be present. In contrast, when an element is referred to as being "directly" "on" another element, there are no intervening elements. Furthermore, when an element is referred to as being "on" a reference portion, the element is located above or below the reference portion, and does not necessarily mean that the element is located "above" or "on" in a direction opposite to gravity.

[0019] In the present specification, descriptions merely referred to as “positive electrode active material layer” without the first and second expressions may be applied to the first positive electrode active material layer and the second positive electrode active material layer.

[0020] In this specification, the term "particle size" refers to the average particle size represented by D50. D50 can be defined as the particle size at 50% of the particle size distribution and can be measured using a laser diffraction method. For example, a method for measuring the average particle size (D50) of a positive electrode active material may include dispersing particles of a positive electrode active material in a dispersion medium, introducing the dispersion into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiating the dispersion with an ultrasonic wave of about 28 kHz with an output of 60 W, and then calculating the average particle size (D50) corresponding to 50% of the cumulative volume in the measuring device.

[0021] In this specification, the term "primary particle" refers to a particle that appears to have no grain boundary when observed at a field of view of 5000 to 20000 times using a scanning electron microscope.

[0022] In the present specification, "secondary particles" refer to particles formed by agglomeration of primary particles.

[0023] In this specification, single particle is a term used to distinguish it from positive electrode active material particles in the form of secondary particles produced by agglomeration of tens to hundreds of primary particles generally used in the related art, and is a concept including single particles composed of one primary particle and agglomerated particles of 10 or less primary particles.

[0024] In the present specification, when "particles" are mentioned, it may refer to any one or all of single particles, secondary particles, and primary particles.

[0025] An exemplary embodiment of the present invention provides a positive electrode for a secondary battery, comprising: a current collector; a first positive electrode active material layer disposed on the current collector; and a second positive electrode active material layer disposed on the first positive electrode active material layer, wherein the first positive electrode active material layer and the second positive electrode active material layer each include a single-particle positive electrode active material and a positive electrode active material having a particle size greater than that of the single-particle positive electrode active material, and wherein the porosity of the first positive electrode active material layer is different from the porosity of the second positive electrode active material layer.

[0026] Another exemplary embodiment of the present invention provides a positive electrode for a secondary battery, comprising: a current collector; a first positive electrode active material layer disposed on the current collector; and a second positive electrode active material layer disposed on the first positive electrode active material layer, wherein the first positive electrode active material layer and the second positive electrode active material layer each include a single-particle positive electrode active material and a positive electrode active material having a particle size greater than that of the single-particle positive electrode active material, and wherein a pore area ratio in a cross-sectional image of the second positive electrode active material layer is 1.05 to 3 times the pore area ratio in a cross-sectional image of the first positive electrode active material layer.

[0027] In the above exemplary embodiment, the positive electrode has a structure in which the positive electrode active material layer is two layers, a single particle of positive electrode active material is included in each layer, and two types of positive electrode active materials having different particle sizes are also included. In addition, the porosity of the first positive electrode active material layer is different from the porosity of the second positive electrode active material layer. Preferably, the porosity of the first positive electrode active material layer may be less than the porosity of the second positive electrode active material layer.

[0028] In this way, the porosity of the first positive electrode active material layer that is closest to the current collector in the two-layer structure of the positive electrode active material including the above-mentioned positive electrode active material is made smaller, so that the resistance characteristics of the positive electrode can be improved. As the porosity of the positive electrode active material layer increases or decreases, the pore area ratio in the cross-sectional image of the positive electrode active material layer also increases or decreases. Therefore, when the pore area ratio in the cross-sectional image of the first positive electrode active material layer is made smaller than the pore area ratio in the cross-sectional image of the second positive electrode active material layer, the effect of improving the resistance characteristics of the above-mentioned positive electrode can be similarly obtained. The porosity or pore area ratio in the cross-sectional image as described above can be achieved by the materials of the above-mentioned layers and the manufacturing method described below.

[0029] According to an exemplary embodiment of the present specification, the first and second positive electrode active material layers each include a single-particle positive electrode active material and a positive electrode active material having a particle size larger than that of the single-particle positive electrode active material. Here, the positive electrode active material having a particle size larger than that of the single-particle positive electrode active material exists in the state of secondary particles, meaning that the particle size of the secondary particles is larger than that of the single-particle positive electrode active material. In the present specification, for convenience, the positive electrode active material having a particle size larger than that of the single-particle positive electrode active material is referred to as a large-particle positive electrode active material.

[0030] According to an exemplary embodiment, the particle diameter of the large-particle positive active material may be 2 μm to 15 μm larger than the particle diameter of the single-particle positive active material, for example, 3 μm to 10 μm larger.

[0031] According to one exemplary embodiment, the particle diameter of the large-particle positive active material may be 5 μm to 15 μm, and the particle diameter of the single-particle positive active material may be 2 μm to 7 μm.

[0032] According to an exemplary embodiment, a content ratio of the single particle positive active material and the positive active material having a particle size greater than the single particle positive active material in the second positive active material layer may be 1:9 to 9:1.

[0033] According to an exemplary embodiment, the porosity of the first positive electrode active material layer may be 0.5% to 25%, for example, 0.5% to 20%, specifically 1% to 10% smaller than the porosity of the second positive electrode active material layer.

[0034] For example, the porosity of the first positive electrode active material layer and the second positive electrode active material layer may be 15% to 40%, respectively.

[0035] Here, regarding the porosity, the porosity of the first positive electrode active material layer and the second positive electrode active material layer can be calculated by measuring the weight per unit electrode area with an electronic balance and measuring the cross-sectional thickness of each layer with a scanning electron microscope.

[0036] According to an exemplary embodiment, the pore area ratio of the second positive electrode active material layer may be 1.1 to 2.8 times, 1.3 to 2.8 times, or 1.5 to 2.5 times the pore area ratio in the cross-sectional image of the first positive electrode active material layer.

[0037] Here, the pore area ratio in the cross-sectional image of the first positive electrode active material layer and the second positive electrode active material layer is calculated by the following method: a cross-sectional sample is produced from the electrode sample in a direction perpendicular to the surface direction and an image is obtained after setting a magnification of 1.00k to 2.00k and measuring the cut surface by a scanning electron microscope with an accelerating voltage of 5kV.

[0038] At this time, when preparing the cross-sectional sample, PDMS resin was used and dried at room temperature under reduced pressure for 48 hours. Thereafter, Ar+ ion milling was performed at an acceleration voltage of 6 kV using Hitachi IM 5000 to produce a cross-sectional sample.

[0039] If the above porosity range is met, the effect of reducing the interface resistance can be expected by reducing the porosity of the first positive electrode active material layer to improve the contact between the current collector and the positive electrode active material. In addition, since the porosity of the second positive electrode active material layer can be relatively increased, the impregnation of the electrolyte solution is promoted, and a favorable effect on the electrode life can be obtained.

[0040] In addition, when the pore area ratio in the above-mentioned cross-sectional image is satisfied, the pore area ratio in the cross-sectional image of the second positive electrode active material layer has a larger value than the pore area ratio in the cross-sectional image of the first positive electrode active material layer. As described above, when the porosity of the positive electrode active material layer increases or decreases, the pore area ratio in the cross-sectional image of the positive electrode active material layer also increases or decreases, so that the advantages obtained when the above-mentioned porosity range is satisfied can be obtained.

[0041] According to an exemplary embodiment, the content of the single-particle positive active material in the first positive active material layer may be greater than that in the second positive active material layer. Thus, the porosity of the first positive active material layer may be controlled to be lower than that of the second positive active material layer.

[0042] Specifically, the content ratio of the single-particle positive electrode active material and the positive electrode active material having a particle size larger than the single-particle positive electrode active material in the first positive electrode active material layer may be 5:5 to 9:1, for example, 6:4 to 9:1, or 7:3 to 9:1, and the content ratio of the single-particle positive electrode active material and the positive electrode active material having a particle size larger than the single-particle positive electrode active material in the second positive electrode active material layer may be 1:9 to 5:5, for example, 1:9 to 4:6, or 1:9 to 3:7.

[0043] When the above range is met, single particles with low porosity will be applied to the first positive electrode active material layer at a high content ratio, and large particles that can be applied without breaking due to their high porosity will be applied to the second positive electrode active material layer at a high content ratio, resulting in reduced diffusion resistance.

[0044] According to an exemplary embodiment, the single particle or large particle positive electrode active material may include a lithium composite transition metal compound including nickel (Ni) and cobalt (Co). The lithium composite transition metal compound may further include at least one of manganese and aluminum. The lithium composite transition metal compound may include 80 mol% or more, for example, 80 mol% or more and less than 100 mol% of nickel in the metal other than lithium. For example, the lithium composite transition metal compound may be composed of Lia Ni (1-x-y) Co x M1 y M2 w A positive electrode active material represented by O2 (1.0 ≤ a ≤ 1.5, 0 < x ≤ 0.2, 0 ≤ y ≤ 0.2, 0 ≤ w ≤ 0.1, 0 < x + y ≤ 0.2, M1 is at least one metal selected from Mn and Al, and M2 is one or more metal elements selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb, and Mo).

[0045] The thicknesses of the first positive electrode active material layer and the second positive electrode active material layer can be 10 μm or more and 500 μm or less, respectively.

[0046] Based on 100 parts by weight of the positive electrode active material layer, the content of the positive electrode active material can be 80 parts by weight or more and 99.9 parts by weight or less, and is preferably 80 parts by weight or more and 99 parts by weight or less.

[0047] According to another exemplary embodiment of the present specification, the positive electrode active material layer of the above exemplary embodiment may further include a positive electrode binder and a conductive material.

[0048] The positive electrode binder can be used to improve the adhesion between positive electrode active material particles and the adhesion force between positive electrode active material particles and the positive electrode current collector. For the positive electrode binder, those known in the art can be used. Non-limiting examples thereof may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one of them or a mixture of two or more of them can be used.

[0049] Based on 100 parts by weight of the positive electrode active material layer, the content of the positive electrode binder can be 0.1 part by weight or more and 50 parts by weight or less, for example, preferably 0.3 part by weight or more and 35 parts by weight or less, and more preferably 0.5 part by weight or more and 20 parts by weight or less.

[0050] The conductive material contained in the positive electrode active material layer is used to impart conductivity to the electrode, and can be used without particular limitation as long as the conductive material has electronic conductivity without causing chemical changes in the battery. Specific examples may include: graphite, such as natural graphite and artificial graphite; carbon-based materials, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, etc., and any one of them or a mixture of two or more thereof may be used.

[0051] Specifically, in an exemplary embodiment, the conductive material may include one or more of single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT). Based on 100 parts by weight of the composition for the positive electrode active material layer, the content of the conductive material may be 0.1 parts by weight or more and 5 parts by weight or less, for example, preferably 0.3 parts by weight or more and 3 parts by weight or less, and more preferably 0.5 parts by weight or more and 2 parts by weight or less.

[0052] There is no particular limitation on the positive electrode current collector, as long as it has conductivity without causing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., etc., can be used. In addition, the positive electrode current collector may generally have a thickness of 1 μm to 500 μm, and the surface of the current collector may be formed with microscopic concavoconvex objects to enhance the adhesion of the positive electrode active material. For example, the positive electrode current collector may be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0053] Another exemplary embodiment of the present specification provides a secondary battery including the positive electrode of the above exemplary embodiment, a negative electrode, and a separator.

[0054] The negative electrode may include a current collector and a negative electrode active material layer disposed on the current collector.

[0055] According to one exemplary embodiment, the negative electrode includes a silicon-based active material.

[0056] In one exemplary embodiment, the silicon-based active material includes SiO x (0≤x<2),SiM y (M is a metal, 1≤y≤4) and at least one of Si / C. The silicon-based active material may include only one type, or two or more types.

[0057] Contains SiO x (0≤x<2) The active material as the silicon-based active material may be a material containing SiO x(0 < x < 2) and silicon-based composite particles with pores.

[0058] SiO x (0 < x < 2) corresponds to the matrix in the silicon-based composite particles. SiO x (0 < x < 2) can be in the form including Si and SiO2, and Si can also form a phase. That is, x corresponds to the ratio of the number of O to Si contained in SiO x (0 < x < 2). When the silicon-based composite particles include SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.

[0059] The silicon-based composite particles may further include at least one of a Mg compound and a Li compound. The Mg compound and the Li compound can correspond to the matrix in the silicon-based composite particles.

[0060] The Mg compound and / or the Li compound may be present in SiO x (0 < x < 2) and / or on the surface of SiO x (0 < x < 2). Through the Mg compound and / or the Li compound, the initial efficiency of the battery can be improved.

[0061] The Mg compound may include at least one selected from the group consisting of Mg silicate, Mg silicide, and Mg oxide. The Mg silicate may include at least one of Mg2SiO4 and MgSiO3. The Mg silicide may include Mg2Si. The Mg oxide may include MgO.

[0062] In an exemplary embodiment of the present specification, based on a total of 100% by weight of the silicon-based active material, the content of the Mg element may be 0.1% to 20% by weight, or 0.1% to 10% by weight. Specifically, the content of the Mg element may be 0.5% to 8% by weight or 0.8% to 4% by weight. When the above range is satisfied, the Mg compound can be included in the silicon-based active material in an appropriate content, so that the volume change of the silicon-based active material during the charge and discharge processes of the battery can be easily suppressed, and the discharge capacity and the initial efficiency of the battery can be improved.

[0063] The Li compound may include at least one selected from the group consisting of Li silicate, Li silicide, and Li oxide. The Li silicate may include at least one of Li2SiO3, Li4SiO4, and Li2Si2O5. The Li silicide may include Li7Si2. The Li oxide may include Li2O.

[0064] In an exemplary embodiment of the present invention, the Li compound may include the form of lithium silicate. The lithium silicate is composed of Li a Sib O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5) indicates that it can be divided into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate can exist in the silicon-based composite particles in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5, and the amorphous lithium silicate can be in the form of Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5). However, the present invention is not limited thereto.

[0065] In an exemplary embodiment of the present specification, based on a total of 100% by weight of the silicon-based active material, the content of the Li element can be 0.1% by weight to 20% by weight, or 0.1% by weight to 10% by weight. Specifically, the content of the Li element can be 0.5% by weight to 8% by weight, and more specifically 0.5% by weight to 4% by weight. When the above range is satisfied, the Li compound can be included in the silicon-based active material in an appropriate content, so that the volume change of the negative electrode active material during the charge and discharge process of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0066] The content of the Mg element or the Li element can be confirmed by ICP analysis. For ICP analysis, a predetermined amount (about 0.01 g) of the negative electrode active material is accurately taken, transferred to a platinum crucible and completely decomposed on a hot plate by adding nitric acid, hydrofluoric acid or sulfuric acid thereto. Thereafter, a reference calibration curve is prepared by measuring the intensity of a standard liquid obtained using a standard solution (5 mg / kg) at the inherent wavelength of the Mg element or the Li element using an inductively coupled plasma atomic emission spectrometer (ICP-AES, Perkin-Elmer 7300). Thereafter, the pretreated sample solution and the blank sample are each introduced into the spectrometer, the actual intensity is calculated by measuring the intensity of each component, the concentration of each component is calculated based on the obtained calibration curve, and then converted so that the sum of the calculated concentrations of the multiple components is equal to the theoretical value, and the content of the Mg element or the Li element of the prepared silicon-based active material can be analyzed.

[0067] In an exemplary embodiment of the present specification, a carbon layer can be provided on the surface and / or inside the pores of the silicon-based composite particles. Through the carbon layer, conductivity is imparted to the silicon-based composite particles, and the initial efficiency, life characteristics, and battery capacity characteristics of a secondary battery including the negative electrode active material containing the silicon-based composite particles can be improved. Based on a total of 100% by weight of the silicon-based composite particles, the total content of the carbon layer can be 5% by weight to 40% by weight.

[0068] In an exemplary embodiment of the present specification, the carbon layer may include at least one of amorphous carbon and crystalline carbon.

[0069] The average particle size of silicon active materials (D 50 ) may be 2 μm to 15 μm, specifically 3 μm to 12 μm, more specifically 4 μm to 10 μm. When the above range is met, the side reaction between the silicon-based composite particles and the electrolyte solution can be controlled, and the discharge capacity and initial efficiency of the battery can be effectively achieved.

[0070] In this specification, the average particle size (D50) may be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve of the particles. The average particle size (D50) may be measured using, for example, a laser diffraction method. In the laser diffraction method, particle sizes from the submicron region to several millimeters can generally be measured, and results with high reproducibility and high resolution may be obtained.

[0071] In an exemplary embodiment of the present specification, the negative electrode active material layer including the silicon-based active material may further include a carbon-based active material. In this case, the content of the silicon-based active material may be 1 to 40 parts by weight, for example, 1 to 20 parts by weight, based on a total of 100 parts by weight of the active material included in the negative electrode active material layer including the silicon-based active material.

[0072] In an exemplary embodiment of the present specification, the carbon-based active material may be graphite, and the graphite may be natural graphite, artificial graphite, or a mixture thereof. The content of the carbon-based active material may be 60 parts by weight or more and 99 parts by weight or less based on a total of 100 parts by weight of the negative electrode active material contained in the negative electrode active material layer.

[0073] In an exemplary embodiment of the present specification, in 100 parts by weight of the negative electrode active material layer, the content of the negative electrode active material can be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and most preferably 98 parts by weight or more and 99.9 parts by weight or less.

[0074] According to another exemplary embodiment of the present specification, the negative electrode active material layer may further include a negative electrode binder in addition to the above-mentioned active material.

[0075] The negative electrode binder can be used to improve the adhesion between the negative electrode active material particles and the adhesion between the negative electrode active material particles and the negative electrode current collector. As the negative electrode binder, those known in the art can be used. Its examples may include polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid and its hydrogen is replaced by Li, Na or Ca etc. At least one of the above-mentioned materials in the group consisting of, and may also include its various copolymers.

[0076] The content of the negative electrode binder may be 0.1 parts by weight or more and 20 parts by weight or less, for example, preferably 0.3 parts by weight or more and 20 parts by weight or less, and more preferably 0.5 parts by weight or more and 10 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer.

[0077] The negative electrode active material layer may not contain a conductive material, but if necessary, it may further contain a conductive material. The conductive material contained in the negative electrode active material layer is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery, and for example, graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers or metal fibers; conductive tubes, such as carbon nanotubes; fluorocarbon powder; metal powders such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and conductive materials such as polyphenylene derivatives, etc. Based on 100 parts by weight of the negative electrode active material layer, the content of the conductive material in the negative electrode active material layer can be 0.01 parts by weight to 20 parts by weight, preferably 0.03 parts by weight to 18 parts by weight.

[0078] In an exemplary embodiment of the present specification, the thickness of the negative electrode active material layer may be 50 μm or more and 500 μm or less.

[0079] In an exemplary embodiment, the negative electrode current collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery. For example, as the current collector, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel treated with carbon, nickel, titanium, silver, etc. on each surface can be used. Specifically, as the current collector, a transition metal (such as copper or nickel) that adsorbs carbon well can be used. The thickness of the current collector can be 1 μm to 500 μm. However, the thickness of the current collector is not limited thereto.

[0080] The positive electrode and the negative electrode can be manufactured by a typical manufacturing method of the positive electrode and the negative electrode, except that the aforementioned positive and negative electrode active materials are used. Specifically, the electrode can be manufactured by drying and rolling after the composition for forming an active material layer containing the aforementioned active material and an optional binder and a conductive material is applied to the current collector. In this case, the types and contents of the positive and negative active materials, binders and conductive materials are as described above. The solvent can be a commonly used solvent in the art, such as dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, and any one of them or a mixture of two or more thereof can be used. Considering the coating thickness and preparation yield of the slurry, as long as the amount of the solvent can dissolve or disperse the active material, the conductive material and the binder and then have a viscosity that can show excellent thickness uniformity when the positive and negative electrodes are coated, the amount of the solvent used is sufficient. As another method, the positive and negative electrodes can be manufactured by casting the composition for forming an active material layer on a separate support and laminating the film obtained by peeling off from the support on the current collector.

[0081] Another exemplary embodiment of the present specification provides a method for manufacturing a positive electrode for a secondary battery of the exemplary embodiment described above. The manufacturing method includes coating a first composition comprising a single-particle positive electrode active material and a positive electrode active material having a particle size larger than that of the single-particle positive electrode active material on a current collector and rolling to form a first positive electrode active material layer; and coating a second composition comprising a single-particle positive electrode active material and a positive electrode active material having a particle size larger than that of the single-particle positive electrode active material on the first positive electrode active material layer and rolling to form a second positive electrode active material layer having a porosity different from that of the first positive electrode active material layer.

[0082] In addition to the above-mentioned positive electrode active material, the compositions for forming the first and second positive electrode active material layers may each further include the above-mentioned binder and conductive material, etc. If necessary, the above-mentioned solvent may be further included.

[0083] In the above-mentioned manufacturing method, rolling is performed after coating in each step when forming the first positive electrode active material layer and the second positive electrode active material layer. By adjusting the rolling conditions at each stage, the porosity of each positive electrode active material layer can be controlled. For example, a condition in which the linear pressure during rolling in the step of forming the second positive electrode active material layer is higher than the linear pressure during rolling in the step of forming the first positive electrode active material layer can be applied. Specifically, the first positive electrode active material layer can be rolled at a low linear pressure of, for example, 1 ton / cm to 1.5 tons / cm, and the second positive electrode active material layer can be further rolled at a high linear pressure of, for example, 1.5 tons / cm to 2.5 tons / cm.

[0084] The type of active material of each positive active material layer and the manufacturing method of performing separate rolling when forming each positive active material layer can make the porosity of the first positive active material layer different from the porosity of the second positive active material layer, and specifically smaller than the porosity of the second positive active material layer.

[0085] The separator is used to separate the negative electrode from the positive electrode and provide a mobile channel for lithium ions, wherein as a separator, any separator can be used without particular restriction, as long as it is generally used in a secondary battery, and in particular, preferably with a high electrolyte solution water retention capacity and a separator with low resistance to ion movement in the electrolyte. Specifically, a porous polymer film can be used, for example, a porous polymer film formed by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure of more than two layers thereof. In addition, conventional porous non-woven fabrics can also be used, for example, non-woven fabrics made of glass fibers and polyethylene terephthalate fibers with high melting points. In addition, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator with a single layer or multilayer structure can be selectively used.

[0086] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used to prepare lithium secondary batteries, but are not limited thereto.

[0087] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0088] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate or ethyl propionate can be used.

[0089] Particularly, in carbonate organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents, and can be preferably used, because it has high dielectric constant and dissociates lithium salt well.When cyclic carbonate is mixed with low viscosity and low dielectric constant straight chain carbonate (such as dimethyl carbonate and diethyl carbonate) in appropriate ratio and used, electrolyte with high conductivity can be prepared, thus can be more preferably used.

[0090] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily dissolved in a non-aqueous electrolyte solution. For example, as the anion of the lithium salt, a metal salt selected from the group consisting of F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - One or more of the groups consisting of.

[0091] For the purpose of improving the service life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, the electrolyte may further include one or more additives, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glycol dimethyl ether, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride.

[0092] The secondary battery according to the exemplary embodiment of the present invention includes an assembly including a positive electrode, a negative electrode, a separator, and an electrolyte, and may be a lithium secondary battery.

[0093] Another exemplary embodiment of the present invention provides a battery module including the above-mentioned lithium secondary battery as a unit cell, and a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries with high capacity, high rate capacity and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.

[0094] Since the secondary battery of the exemplary embodiment of the present invention stably exhibits excellent discharge capacity, output characteristics and cycle performance, the lithium secondary battery can be used as a power source for portable devices such as mobile phones, notebook computers and digital cameras, and medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems. For example, the battery module or battery pack can be used as a power source for one or more of the following medium and large devices: power tools; electric vehicles including electric vehicles (EV), hybrid electric vehicles and plug-in hybrid electric vehicles (PHEV); and power storage systems.

[0095] Example

[0096] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are only used to illustrate the present invention, and various modifications and changes can be made within the scope and technical spirit of the present invention. Such modifications and changes naturally fall within the scope of the claims included herein.

[0097] Example 1

[0098] Slurries for forming a first positive electrode active material layer and a second positive electrode active material layer on a positive electrode current collector were prepared separately and coated as follows. After coating the first positive electrode active material layer, it was dried by a drying furnace at a speed of 30 m / min. Then, the linear pressure was adjusted and hot rolling was performed at a temperature of 90°C. Subsequently, the second positive electrode active material layer was coated using the same method, the linear pressure was adjusted and hot rolling was performed at a temperature of 90°C, thereby preparing an electrode including a first positive electrode active material layer with a porosity of 20% and a second positive electrode active material layer with a porosity of 24%.

[0099] As a composition for preparing the first positive electrode active material layer and the second positive electrode active material layer, a positive electrode slurry obtained by adding a Ni-based positive electrode active material, a conductive material (CNT) and a binder (PVDF) to a methylpyrrolidone (NMP) solvent at a weight ratio of 97.0:1:2 was used. The Ni-based positive electrode active material of the composition for the first positive electrode active material layer includes a single-particle positive electrode active material and a large-particle positive electrode active material at a weight ratio of 8:2, and the Ni-based positive electrode active material of the composition for the second positive electrode active material layer includes a single-particle positive electrode active material and a large-particle positive electrode active material at a weight ratio of 2:8.

[0100] For the single-particle positive electrode active material, a composition of Li 1.0 Ni 0.86 Co 0.08 Mn 0.06 O2 and a Ni-based positive electrode active material with a particle size of 4 μm. For large-particle positive electrode active materials, a composition of Li 1.0 Ni 0.87 Co 0.04 Mn 0.07 Al 0.02 O2 and a Ni-based positive electrode active material with a particle size of 9μm.

[0101] The porosity of the positive electrode prepared above is shown in Table 1 below.

[0102] A composition comprising a negative electrode slurry obtained by adding a negative electrode active material, a conductive material (carbon black), a binder (SBR) and a thickener (CMC) to a distilled water solvent in a weight ratio of 96:1:2:1 was coated on a negative electrode collector, and then dried and roll-pressed to prepare a negative electrode, wherein the negative electrode active material comprises SiO-based and carbon-based (comprising artificial graphite and natural graphite) active materials (the content of the SiO-based active material is 5 parts by weight based on 100 parts by weight of the total negative electrode active material).

[0103] The positive electrode and the negative electrode were stacked with a separator inserted therebetween, and an electrolyte solution consisting of 1M LiPF6, ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (volume ratio 3 / 7), vinylene carbonate (VC) / propane sultone (PS) (3 parts by weight and 1.5 parts by weight, respectively, based on 100 parts by weight of the total electrolyte) was injected to prepare a battery.

[0104] Example 2

[0105] The same procedure as in Example 1 was performed, except that the porosity of the first positive electrode active material layer was 30% lower than the porosity of the second positive electrode active material layer.

[0106] Example 3

[0107] The same procedure as in Example 1 was performed, except that the weight ratio of the single-particle positive electrode active material to the large-particle positive electrode active material in the first positive electrode active material layer was 2:8, and the weight ratio of the single-particle positive electrode active material to the large-particle positive electrode active material in the second positive electrode active material layer was 8:2.

[0108] Comparative Example 1

[0109] The same procedure as in Example 1 was performed except that coating of the first positive electrode active material layer was performed using one slurry containing the single-particle positive electrode active material and the large-particle positive electrode active material in a weight ratio of 8:2.

[0110] Comparative Example 2

[0111] Two positive electrode active material layers with the same porosity were prepared under the following process conditions.

[0112] The slurry of the first positive active material layer and the second positive active material layer was prepared as follows and coated on the positive current collector. After coating each layer of the first positive active material layer and the second positive active material layer, they were dried by a drying oven at a speed of 30 m / min. Then, the linear pressure was adjusted and hot rolling was performed at a temperature of 90°C to produce an electrode with a porosity of 24%.

[0113] The same procedure as in Example 1 was performed, except that the slurry was prepared while the weight ratio of the single-particle positive electrode active material to the large-particle positive electrode active material of the first positive electrode active material layer was set to 2:8, and the weight ratio of the single-particle positive electrode active material to the large-particle positive electrode active material of the second positive electrode active material layer was set to 8:2.

[0114] Comparative Example 3

[0115] Two positive electrode active material layers having the same porosity were prepared by the following method.

[0116] The slurry of the first positive active material layer and the second positive active material layer was prepared as follows and coated on the positive current collector. After each layer of the first positive active material layer and the second positive active material layer was coated simultaneously, they were dried by a drying oven at a speed of 30 m / min. Then, the linear pressure was adjusted and hot rolling was performed at a temperature of 90°C to produce an electrode with a porosity of 24%.

[0117] The same process as in Example 1 is performed, except that the Ni-based positive electrode active material layer of the composition for the first positive electrode active material layer contains a single-particle positive electrode active material and a large-particle positive electrode active material in a weight ratio of 8:2, and the Ni-based positive electrode active material of the composition for the second positive electrode active material layer is prepared using a slurry containing a single-particle positive electrode active material and a large-particle positive electrode active material in a weight ratio of 2:8.

[0118] Comparative Example 4

[0119] Two positive electrode active material layers having the same porosity were prepared by the following method.

[0120] The slurry of the first positive active material layer and the second positive active material layer was prepared as follows and coated on the positive current collector. After each layer of the first positive active material layer and the second positive active material layer was coated simultaneously, they were dried by a drying oven at a speed of 30 m / min. Then, the linear pressure was adjusted and hot rolling was performed at a temperature of 90°C to produce an electrode with a porosity of 24%.

[0121] The same procedure as in Example 1 is performed, except that the Ni-based positive electrode active material of the composition for the first positive electrode active material layer comprises a single-particle positive electrode active material, and the Ni-based positive electrode active material of the composition for the second positive electrode active material layer is prepared using a slurry comprising a single-particle positive electrode active material and a large-particle positive electrode active material in a weight ratio of 2:8.

[0122] Comparative Example 5

[0123] Two positive electrode active material layers having the same porosity were prepared by the following method.

[0124] The slurry of the first positive active material layer and the second positive active material layer was prepared as follows and coated on the positive current collector. After each layer of the first positive active material layer and the second positive active material layer was coated simultaneously, they were dried by a drying oven at a speed of 30 m / min. Then, the linear pressure was adjusted and hot rolling was performed at a temperature of 90°C to produce an electrode with a porosity of 24%.

[0125] The same procedure as in Example 1 is performed, except that the Ni-based positive electrode active material of the composition for the first positive electrode active material layer includes a single-particle positive electrode active material and a large-particle positive electrode active material in a weight ratio of 8:2, and the Ni-based positive electrode active material of the composition for the second positive electrode active material layer is prepared using a slurry including a single-particle positive electrode active material.

[0126] [Table 1]

[0127]

[0128] Figure 1 The resistance values ​​of the batteries prepared in Examples 1 to 3 and Comparative Examples 1 to 5 as a function of the state of charge (SOC) are shown. It can be confirmed that Examples 1 to 3 exhibit excellent resistance characteristics at all states of charge (SOC) compared with Comparative Examples 1 to 5. In this case, the resistance is measured by subjecting the prepared battery cell to constant current / constant voltage (CC / CV) charging (0.05C-cutoff) to 4.2V at 0.33C and constant current (CC) discharge (2.5V-cutoff) at 0.33C for 3 times, discharging the battery cell to 0.33C after charging, setting each SOC (%) and performing pulse discharge at 2.5C for 10 seconds.

Claims

1. A positive electrode for a secondary battery, comprising: current collector; a first positive electrode active material layer disposed on the current collector; as well as a second positive electrode active material layer disposed on the first positive electrode active material layer, wherein the first positive electrode active material layer and the second positive electrode active material layer each contain a single particle positive electrode active material and a positive electrode active material having a particle size larger than that of the single particle positive electrode active material, and The porosity of the first positive electrode active material layer is different from the porosity of the second positive electrode active material layer.

2. A positive electrode for a secondary battery, comprising: current collector; a first positive electrode active material layer disposed on the current collector; and a second positive electrode active material layer disposed on the first positive electrode active material layer, wherein the first positive electrode active material layer and the second positive electrode active material layer each include a single particle positive electrode active material and a positive electrode active material having a particle size larger than that of the single particle positive electrode active material, and The pore area ratio in the cross-sectional image of the second positive electrode active material layer is 1.05 to 3 times the pore area ratio in the cross-sectional image of the first positive electrode active material layer.

3. The positive electrode for a secondary battery according to claim 1, wherein The porosity of the first positive electrode active material layer is smaller than the porosity of the second positive electrode active material layer.

4. The positive electrode for a secondary battery according to claim 1, wherein The porosity of the first positive electrode active material layer is lower than the porosity of the second positive electrode active material layer by 0.5% to 25%.

5. The positive electrode for a secondary battery according to claim 1, wherein The porosity of the first positive electrode active material layer and the second positive electrode active material layer are respectively 15% to 40%.

6. The positive electrode for a secondary battery according to claim 1, wherein The particle size of the positive electrode active material in the first positive electrode active material layer and the second positive electrode active material layer is larger than the particle size of the single positive electrode active material particle by 2 μm to 15 μm.

7. The positive electrode for a secondary battery according to claim 1, wherein In the first positive electrode active material layer and the second positive electrode active material layer, a content ratio of the single-particle positive electrode active material to a positive electrode active material having a particle size larger than that of the single-particle positive electrode active material is 1:9 to 9:

1.

8. The positive electrode for a secondary battery according to claim 1, wherein The content of the single-particle positive electrode active material in the first positive electrode active material layer is greater than the content of the single-particle positive electrode active material in the second positive electrode active material layer.

9. The positive electrode for a secondary battery according to claim 1, wherein The content ratio of the single-particle positive electrode active material in the first positive electrode active material layer to the positive electrode active material having a particle size larger than that of the single-particle positive electrode active material is 5:5 to 9:1, and the content ratio of the single-particle positive electrode active material in the second positive electrode active material layer to the positive electrode active material having a particle size larger than that of the single-particle positive electrode active material is 1:9 to 5:

5.

10. The positive electrode for a secondary battery according to claim 1, wherein The first positive electrode active material layer and the second positive electrode active material layer include a lithium composite transition metal compound including nickel (Ni) and cobalt (Co).

11. The positive electrode for a secondary battery according to claim 10, wherein The lithium composite transition metal compound further includes at least one of manganese and aluminum.

12. A secondary battery comprising: The positive electrode according to any one of claims 1 to 11, negative electrode, and Diaphragm.

13. The secondary battery according to claim 12, wherein: The negative electrode includes a silicon-based active material.

14. The secondary battery according to claim 13, wherein The negative electrode further comprises a carbon-based active material.

15. A method for manufacturing a positive electrode for a secondary battery according to any one of claims 1, 3 to 11, the method comprising: coating a first composition including a single particle positive electrode active material and a positive electrode active material having a particle size larger than that of the single particle positive electrode active material on a current collector and rolling the composition to form a first positive electrode active material layer; as well as A second composition including a single-particle positive electrode active material and a positive electrode active material having a particle size larger than that of the single-particle positive electrode active material is coated on the first positive electrode active material layer and roll-pressed to form a second positive electrode active material layer having a porosity different from that of the first positive electrode active material layer.

16. The method according to claim 15, wherein: A linear pressure during roll pressing when forming the second positive active material layer is higher than a linear pressure during roll pressing when forming the first positive active material layer.

Citation Information

Patent Citations

  • Refrigerator and method for controlling refrigerator

    KR1020220128886A

  • Method and apparatus for hybrid automatic repeat request in multi connected environment

    KR1020230131799A